Using the System Dynamic Approach to Develop a Policy Scenario for Reducing CO2 Emissions from Tourism Travel - SUSANTY, Aries; BAKTHTIAR, Arfan; PUSPITASARI, Nia Budi; PRASETYO, Siddiq (Journal of Environmental Management and Tourism, 2019)
This study has several purposes. The first is to determine the causal relationship between tourist transportation behaviour, the number of tourists, and the volume of CO 2 emissions produced from tourist transportation to the Borobudur Temple. The second purpose is to use a system dynamic methodology to simulate a reduction in the amount of CO 2 emissions from tourist transportation to the Borobudur Temple. Lastly, to identify the best policy with which to regulate tourist transportation to the Borobudur Temple. To achieve those purposes, the r eal systems are identified and translated into system dynamic models using causal-loop and stock-and-flow diagrams. The model consists of three sub-systems, i.e., the number of tourists, the modes of transportation, and the volume of CO 2 emissions. Moreover, this study generated eight scenarios for comparison with respect to the volume of CO 2 emissions resulting from several transportation modes. The result of simulation with system dynamic methodology indicated that t he CO 2 emissions produced by scenarios 1, 2, 3, and 4 are within the range of 1,800,000 kg CO 2 , which means that they approach the target of reducing CO 2 emissions by 50% by 2035. This study provides essential insights for governmental and local authorities with respect to policy implementation.